#TITLE_ALTERNATIVE# - Satria NIM. 23197050, Iman
Abstract: The dynamic characteristics of a rail vehicle is, to a certain extent, governed by the design of its bogie and corresponding dynamic parameters. Bogie that consists of frame and suspension system connecting wheelset to carbody, and plays an important role in determining the maximum safe operating speed, known as critical speed, Vacr Operation beyond this critical speed will result in unstable lateral motion or hunting of the vehicle which could lead to wheel-climb. The spectrum and magnitude of vibration response of the vehicle due to wheel-rail interaction determine the ride comfort, Assessment of whether the safety and comfort criteria have been met is conducted through evaluation of the vehicle lateral stability and its dynamic response. In this investigation, the rail vehicle is modelled as multibody system consisting if several rigid bodies interconnected by elastic elements, i.e. springs and dampers. Multibody dynamic analysis of the system is performed to obtain the dynamic response and stability evaluation. Influence of varying the bogie dynamic parameters are conducted to determine parameters most responsible. The parameters are the primary and secondary suspensions lateral, longitudinal and vertical stiffness coefficients, secondary suspension_ damping coefficient, bogie mass, conicity of the wheel and track width. The results show that the critical speed is influenced mostly by the primary suspension lateral stiffness, conicity of the wheel and track width_ The dynamic response due to the track lateral irregularities is also performed.